Development of an anthropomorphic mobile manipulator with human, machine and environment interaction - Gonçalves, Fernando (2019)
An anthropomorphic mobile manipulator robot (CHARMIE) is being developed by the University of Minho's Automation and Robotics Laboratory (LAR). The robot gathers sensorial information and processes using neural networks, actuating in real time. The robot's two arms allow object and machine interaction. Its anthropomorphic structure is advantageous since machines are designed and optimized for human interaction. Sound output allows it to relay information to workers and provide feedback. Allying these features with communication with a database or remote operator results in establishment of a bridge between the physical environment and virtual domain. The goal is an increase in information flow and accessibility. This paper presents the current state of the project, intended features and how it can contribute to the development of Industry 4.0. Focus is given to already finished work, detailing the methodology used for two of the robot's subsystems: locomotion system; lower limbs of the robot.